GENDER, AGEING AND SOCIAL SECURITY - S Irudaya Rajan & Sabu Aliyar
The first part of this paper discusses the emerging profile of the elderly in Kerala for the next fifty years based on the projections done by the authors, followed by the micro analysis of elderly living conditions from the recent migration survey conducted by the Centre for Development Studies. The last section overviews the existing social security program for the elderly. Close to 15 percent of the elderly in Kerala form the creamy layer of senior citizens who are not looking for any assistance from the Kerala government. Even at the age of 80, 10 percent of the elderly continue to work. The paper outlines the fact that if the government can implement all the schemes very seriously and provide assistance to the real needy among the elderly, Kerala can continue to run the social assistance schemes without much financial constraints.